Breathing, Emotion and Evolution - Holstege, G. (Gert); Beers, Caroline M.; Subramanian, Hari H. (Progress in brain research, 2014)
Respiration is one of the most basic motor activities crucial for survival of the individual. It is under total control of the central nervous system, which adjusts respiratory depth and frequency depending on the circumstances the individual finds itself. For this reason this volume not only reviews the basic control systems of respiration, located in the caudal brainstem, but also the higher brain regions, that change depth and frequency of respiration. Scientific knowledge of these systems is crucial for understanding the problems in the many patients suffering from respiratory failure. Th.